Handbook for Improving the Living Conditions of Roma - World Bank (World Bank, Washington, DC, 2014)
A disproportionately large number of Roma in Europe today face deep poverty, social exclusion, and poor living conditions. Improving these is critical to achieving the targets of the Europe 2020 Strategy, the European Union s 10-year growth strategy, which aims to reduce poverty, social exclusion, early school leaving, and increase school attainment and employment by 2020. The EU Framework for National Roma Integration Strategies (NRIS) up to 2020 calls on the European Commission and the member states to mobilize existing EU strategies and instruments in the cause of securing the socioeconomic inclusion of Roma and invites the member states to make sufficient use of EU and national funding to address Roma needs. The implementation and success of the NRIS will very much depend on an effective and sufficient allocation of national resources. EU funding alone can certainly not solve the situation of Roma, but the Commission calls on member states to make efficient use of the funds. The European Structural and Investment (ESI) Funds, principally the European Social Fund (ESF), the European Regional Development Fund (ERDF), and the European Agricultural Fund for Rural Development (EAFRD) generally constitute the EU s main instruments for supporting member states efforts to improve the lives of vulnerable people, including the Roma. These funds will be invested in shared management by the European Commission and the member states and regions through operational programs (OPs) that cover a seven year period between 2014 and 2020. Based on the priorities established in the OPs, the management authorities invest these funds for projects mainly on the basis of calls for proposals (CfPs). The Council of the European Union, through a recommendation on effective Roma integration measures,3 calls on the involvement of local authorities and civil society organizations (CSOs) in developing, implementing, and monitoring national strategies through operations co-financed by the ESI Funds. In this context, this handbook was prepared to help prepare and implement effective interventions for improving the living conditions of disadvantaged Roma at the local level, using European, national, or local funds. While there are legal texts such as (1) Regulations of the European Parliament and of the Council, which lay down the general provisions on the EU funds; (2) country position papers that outline the analysis of the main challenges and funding priorities relevant for the ESI funds; and (3) Guidance on European Structural and Investment Funds 2014 2020 which consist of a series of guidelines and templates for operationalizing the EU policies and regulations, this handbook should be treated as a nonbinding reference source. It shares hands-on, practical knowledge, techniques, and tools for enhancing the quality of interventions. The handbook intends to provide global insights, experience, and ideas to broaden the range of interventions and actions considered by stakeholders, and also to inspire further innovations.